WANPRESTASI PADA LAYANAN PAYLATER DALAM APLIKASI SHOPEE - Rahayu Iftahul Jannah; Ma'ruf Akib; Ismi Fadjriah; Wahyudi Umar (Jurnal Hukum Lex Generalis, 2024)
This study examines the phenomenon of default in the use of the PayLater service on the Shopee application, which is increasingly popular in Indonesia along with the development of e-commerce. The purpose of this study is to analyze the legal consequences of default by debtors in the use of this service. Normative legal research is carried out using a legislative and conceptual approach. The results of this study emphasize that consumers must understand the terms and conditions before using PayLater to avoid legal problems in the future because the results show that default occurs when debtors do not fulfill their payment obligations as agreed, which can result in fines and recording in the Financial Information Service System (SLIK) of the OJK.